A new species of Diatraea Guilding, 1828, feeding on sugarcane from Nayarit, Mexico, and a lectotype designation for Diatraea magnifactella Dyar, 1911 (Lepidoptera, Crambidae, Crambinae) - Robles-Pérez, Rafael; Solis, M. Alma (Zootaxa, 2024)
Between 2022 and 2023, over a thousand larvae and pupae of sugarcane borers in the genus Diatraea Guilding, 1828, were collected in the state of Nayarit, Mexico, and reared to adults to identify them based on the morphology of genitalia. Although two species, Diatraea considerata Heinrich, 1931, and D. magnifactella Dyar, 1911, had been reported to occur in western Mexico, we discovered a new species of sugarcane borer, Diatraea nayaritella Robles & Solis, sp. nov., from Nayarit, Mexico. It had been preliminarily identified as D. considerata, which was described from the state of Sinaloa, Mexico. Additionally, we designate a lectotype for D. magnifactella, new lectotype, from Orizaba, Veracruz, Mexico, to stabilize the name and identity of this species. The distribution of D. magnifactella is discussed.